Pemberdayaan Masyarakat Desa Bandar Tengah Melalui Pelatihan Inovasi Olahan Jahe dan Pemasarannya - Bambang Kurniawan; Tri Wulandari; Meilani Warahmah Ujung; Ilmi Widya Sari; Ariska Munthe; Juli Kartika; Nurhasanah Dwi Khodijah; Aulia Kamal; Ayu Diah Anggraini; Anugrah Perdana Siregar; Tiflatul Husna; Muhammad Noer Fadlan (Westscience Press, 2023)
Program kegiatan